Fire resistance evaluation and minimum reinforcement ratio for hybrid fibre-reinforced RPC beams under fire exposure. (December 2021) - Ren, Pengfei; Hou, Xiaomeng; Cui, Zhongqian; Xie, Hengyan; Abid, Muhammad
Abstract: Reactive powder concrete (RPC) structural members are faced with the problem of fire resistance evaluation in fire safety design. In this study, the fire resistance of hybrid fibre-reinforced RPC beams evaluated through the existing design methods was compared with those measured in standard fire tests. The results showed that the existing design methods cannot provide satisfactory fire resistance evaluation for hybrid fibre-reinforced RPC beams, which highlights the need to propose a new prediction method. To fill this gap, an existing macroscopic finite-element model was extended to simulate the fire response of hybrid fibre-reinforced RPC beams. Based on the developed FE model, an extensive parametric study was conducted to study the effects of structural parameters such as the RPC cover thickness, load ratio, reinforcement ratio, span-depth ratio, beam width and compressive strength of RPC on the fire resistance of hybrid fibre-reinforced RPC beams. Then, through the regression analysis of the 663 FE simulation results, an equation, which is expressed in the form of continuous multiplication, was proposed to predict the fire resistance of hybrid fibre-reinforced RPC beams under standard fire exposure. The validity of the proposed equation was established through comparisons with the results from FE simulation and existing fire resistance tests. Additionally, the minimum reinforcement ratio required for RPC beams to achieve a specified fire resistance was proposed to prevent the brittle failure caused by the insufficiency of reinforcement under fire. Highlights: A finite-element model is extended to simulate fire response of hybrid fibre-reinforced RPC beams. Equation for fire resistance prediction of hybrid fibre-reinforced RPC beams is proposed. Minimum reinforcement ratio required for RPC beams to achieve a specified fire resistance is proposed.